Academia as a league system - Aloys Prinz; Thomas Ehrmann (Journal of Business Economics, 2022)
In this paper, we explain the stability of top university ranks and discuss attempts to create top national universities. Firstly, it is shown theoretically that in a world with differently-gifted poor and rich students, a three-tier university system may become very stable, with a super league of the best research universities that attract the best students, whether rich or poor. Secondly, it is empirically demonstrated that half of the highest ranked universities enjoy very stable competitive advantages. Thirdly, we examine attempts of China, France and Germany to overcome these disadvantages and to get into this super league. The recent attempt of China to create such super league universities shows the financial and societal costs of these attempts. France demonstrates how the concentration of financial resources on two newly built universities that complement the forces of existing ones—either real or only by labelling—may succeed. Despite the complexly designed and competitive German Excellence Initiative, ongoing since 2004, no German university was among the top 50 in the Shanghai ranking in 2021 (compared to one university in 2004). The mixed results of all these worldwide attempts may reflect the problem that late market entry into the super league may be too costly, given that the classical university business model is in the mature phase of its life cycle.
Keywords: A20; F20; H52; I23; I28; M21; 650; University ranking; Super league; Three-tier league; Talent allocation; Students; Researchers